EFFECT OF PROFITABILITY AND LIQUIDITY ON SHARE PRICES (Survey on Industrial Companies of Consumer Goods Listed on Indonesia Stock Exchange Period 2016-2018) - Sukandi, Pipin; Registiany, Via (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to determine how the effect of profitability and liquidity on stock prices in consumer goods industry sector companies listed on the Indonesia Stock Exchange 2016-2018 period. The factors tested in this study are profitability and liquidity as independent variables, while stock price as the dependent variable. The research method used in this research is the verification method. The population in this study is the consumer goods industry sector companies listed on the Indonesia Stock Exchange for the 2016-2018 period, totaling 52 companies. The sampling technique used in this study was non-probability sampling with a purposive sampling method, so that the total sample size was 31 banks. The data analysis used in this study was panel data regression analysis at a significance level of 5%. The program used in analyzing the data used Eviews 9. The results showed that profitability and liquidity had an effect on stock prices. In addition, the research results also show that the magnitude of the influence of profitability and liquidity in giving a contribution of influence on stock prices is 60.4%.